Respiratory burst activity of intestinal macrophages in normal and inflammatory bowel disease. - Mahida, Y; Wu, K; Jewell, D (1989)
Macrophages isolated from normal mucosa (greater than 5 cm from tumour) and inflamed mucosa (from patients with inflammatory bowel disease) of colon and ileum were studied for their ability to undergo a respiratory burst as assessed by reduction of nitroblue tetrazolium to formazan. Using phorbol myristate acetate (PMA) and opsonised zymosan as triggers, only a minority (median: 8% for zymosan and 9% for PMA) of macrophages isolated from normal colonic mucosa demonstrated release of oxygen radicals. In contrast, a significantly greater (median: 17% for zymosan and 45% for PMA) proportion of macrophages isolated from inflamed colonic mucosa were able to undergo respiratory burst. Studies with normal and inflamed ileum showed similar results. Stimulation of macrophages isolated from normal colon with interferon-gamma produced only a small increase in the proportion of cells showing release of oxygen radicals. We conclude that the respiratory burst capacity of majority of macrophages isolated from normal colon and ileum is downregulated and a greater proportion of macrophages isolated from inflamed colon and ileum are able to undergo a respiratory burst.